2018
DOI: 10.1111/imj.13738
|View full text |Cite
|
Sign up to set email alerts
|

Music reduces state anxiety scores in patients undergoing pleural procedures: a randomised controlled trial

Abstract: Listening to music appears to be beneficial in reducing anxiety in patients undergoing pleural procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
(85 reference statements)
0
8
0
Order By: Relevance
“…As such, it is an essential element in motivation, and plays an important role in human evolutionary history 11 . There are numerous studies reporting short‐ and long‐term beneficial effects of music in patients suffering from depression, anxiety, or even schizophrenia 12–14 . Live music therapy was shown to be effective in reducing distress and pain in young children after burn wound care 15 .…”
Section: Beatles Songs In Medical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, it is an essential element in motivation, and plays an important role in human evolutionary history 11 . There are numerous studies reporting short‐ and long‐term beneficial effects of music in patients suffering from depression, anxiety, or even schizophrenia 12–14 . Live music therapy was shown to be effective in reducing distress and pain in young children after burn wound care 15 .…”
Section: Beatles Songs In Medical Studiesmentioning
confidence: 99%
“…11 There are numerous studies reporting short-and long-term beneficial effects of music in patients suffering from depression, anxiety, or even schizophrenia. [12][13][14] Live music therapy was shown to be effective in reducing distress and pain in young children after burn wound care. 15 Moreover, it was recently demonstrated that long-term music exposure is effective in preventing age-related cognitive deficits in rats, suggesting that music exposure has also selective effects on cognitive functions.…”
Section: Beatles Songs In Medical Studiesmentioning
confidence: 99%
“…In addition, seven studies failed to blind the participants and investigators (Cakmak et al, 2017;Lopez-Yufera et al, Nurse Media Journal of Nursing, 12(3), 2022, 427 . In terms of detection bias, five studies were considered as high risk (Cakmak et al, 2017;Mackintosh et al, 2018;Tolunay et al, 2018;Wazzan et al, 2022; W. L. , and the risk of bias was unclear for one study (Wu et al, 2017). The remaining six studies were evaluated as low risk of bias.…”
Section: Risk Of Bias For the Included Studiesmentioning
confidence: 99%
“…There was one study in a radiology department that provided meditative music during tomography scans (W. L. . One study provided intraoperative music (Mackintosh et al, 2018), and the final study provided music in a post-anesthesia care unit (PACU) (W. P. .…”
Section: Characteristics Of the Studymentioning
confidence: 99%
See 1 more Smart Citation